Linkage to methadone treatment from acute opiate detoxification treatment - Zaller, PhD, Nickolas D.; Thurmond, MPH, Portia; Brett, PhD, Jon; Carleton, MS, James C.; Rich, MD, MPH, Josiah D. (Journal of Opioid Management, 2006)
Methadone maintenance treatment (MMT) is a safe pharmacological treatment strategy for addiction to heroin and other opiates; however, linking individuals to MMT is often challenging. We present results from a pilot project (Project VISTA) funded by the Center for Substance Abuse Treatment that helps heroin-dependent injection drug users (IDUs) transition from acute heroin detoxification to MMT. Participants are referred to Project VISTA by the state detoxification center, and Project VISTA facilitates entry into an MMT program, providing full financial support for up to 24 weeks. In addition, Project VISTA provides case management and referral to ancillary services such as housing, other medical care, and mental health treatment. From May 2005 to May 2006, 60 individuals were enrolled in Project VISTA. A total of 41 participants (69.5 percent) remained in treatment for at least 24 weeks, with a mean number of weeks in treatment of 31. A Kaplan-Meier analysis was performed on all participants, and the incidence of individuals being discharged from treatment was 2 percent per week. Project VISTA, in cooperation with the state detoxification center and a Providence-based MMT program, has created a model that provides continuity of treatment services to high-risk, HIV-negative IDUs. Our model demonstrates that through facilitating the transition from an opiate detoxification program into an MMT program, individuals with chronic heroin addiction can successfully access and engage in treatment.